Development of microstructure - processing correlations of Inconel718 through additive manufacturing. (2022) - Dharmalingam, G.; Baskar, R.; Arun Prasad, M.; Salunkhe, Sachin
Abstract: Processing of nickel based superalloy for high temperature applications developed through cast route is one of the most challenging tasks in the manufacturing industry. Since, nickel super alloys consists of good corrosion, oxidation, wear resistance and room / high temperature mechanical properties, it is widely used in rocket engines, launch vehicles, gas turbines, aeronautical and nuclear reactors, etc. Cast defects, post-processing through machining and design of complex structures are limited while manufacturing through conventional methods. To overcome these drawbacks, additive manufacturing technique is used to manufacture Inconel-718 (IN718) superalloy through direct metal laser sintering (DMLS). Microstructure, property and processing correlation of IN718 superalloy were carried out in the present study. Moreover, it is also compared with cast product to understand the effects of additive manufacturing on IN718 superalloy before post processing. The microstructures, property of as built IN718 superalloy were evaluated using optical microscopy (OM), scanning electron microscopy (SEM) and Vickers hardness tester. The additively manufactured sample IN718 (DMLS) showed higher hardness than cast Inconel718, because of fine grained microstructure.